Extended school day and teenage fertility in Dominican Republic - Santiago Garganta; María Florencia Pinto; Joaquín Zentner (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2023)
This paper investigates the potential impact of extended school days in reducing teenage fertility. We study the Jornada Escolar Extendida program, which doubled the school-day length from 4 to 8 hours in the Dominican Republic, and exploit the geographic and time variation induced by its gradual implementation. We find evidence that a higher exposure to JEE in the municipality, measured as the percentage of secondary students covered by the program, reduces the incidence of teenage pregnancies, and that the effect is stronger after the program has reached at least half of secondary students in the municipality. The estimates are robust to various specifications and alternative checks. These results suggest that extended school-day policies can have spillover effects regarding teenagers' fertility choices.
Keywords: H52; I18; I28; J13; O15; 330; School day extension; risky behavior; teenage fertility; Dominican Republic